Help heal yourself from cancer : partner smarter with your doctor, personalize your treatment plan, and take charge of your recovery - Sears, William, 1939-; Sears, Martha (BenBella Books, Inc., 2022)
"In Help Heal Yourself from Cancer, cancer survivors and medical-profession veterans Bill and Martha Sears help you go from patient to partner in your cancer-healing journey. They outline the steps you can take, both in working with your cancer-care providers and on your own, to maximize your chances of not just beating cancer, but thriving in its wake"--